Pola Interaksi Spasial serta Karakteristik Individu dan Rumah Tangga Komuter antar Kabupaten/Kota di Bandung Raya - Riya Supriyatin; Andrea Emma Pravitasari; Didit Okta Pribadi (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2020)
Spatial Interaction Pattern and Characteristics of Individual and Household Commuters between Regencies/Cities in Greater Bandung Differences in regional development in Greater Bandung caused spatial interaction in order to meet the shortcomings in origin areas. One of the form spatial interaction is commuting. This study aimed to analyze the pattern of spatial interaction between regencies/cities in Greater Bandung and determine individual and household commuter characteristics. Variables used to analyze the pattern of spatial interactions were number of commuters, distances, regional development index, built up area ratio, and population density of regency/city units in Greater Bandung. Method used were Entropy Index and Augmented Doubly Constrained Entropy Model. Variables used to determine individual and household commuter characteristics were age, marital status, highest education completed, number of household members, monthly household expenditure, and the main reason for choosing settlement location. Data were originated from 2017 Greater Bandung Commuter Survey held by Statistics Indonesia (BPS), which consists of 15,082 individuals and 4,531 households. The method used was correspondence analysis. Analysis results shows that Bandung Regency, Sumedang Regency, and Bandung City had positive effects on spatial interactions in Greater Bandung. Commuters in Greater Bandung mostly come from regency areas with productive age, low education level, big number of household members, have low and high economic level, live in regency area because of affordable house price and closeness to family. Meanwhile, commuters in Greater Bandung mostly move toward city areas have young and productive age, high education level, have low and high economic level, and variety number of household members.